A concise, engaging, yet somewhat limited introduction to a thematic hot potato (KULT_online, 2014)
Markus Tauschek’s Kulturerbe is one of the latest offerings from Reimer’s Kulturwissenschaften series and serves as a general introduction to Kulturerbe (cultural heritage) from the perspective of cultural anthropology. The author begins by addressing the apparent ubiquity of cultural heritage, its definition, the history of its usage (mostly within the German speaking sphere), its inextricable entanglement with monuments, conservation initiatives, museologising, memory, UNESCO, and world heritage. He also considers the material and immaterial implications of the forms taken by cultural heritage, not to mention questions of ownership, the relationship it has with tourism and, finally, the emerging field of critical heritage studies. In bringing together such a broad array of themes crucial for the understanding of such a thematic hot potato in such a short volume, this work is an achievement in the field of short introductory texts.